Gender-Based Violence Cases Recorded at One-Stop Crisis Management Center (OCMC) of a Provincial Hospital of Nepal, a Descriptive Study - Sharma, Suraj; Pyakurel, Manaswi; Shrestha, Amrita; Katwal, Barshika; Shrestha, Niranjan (Nepal Medical College Journal, 2025)
The term “violence” denotes an act of physical force that causes or is intended to cause harm. Gender-based violence is a worldwide problem and has been affecting 1 (35.00%) in three women in their lifetime. Following cases fall under GBV in Nepal: rape, sexual abuse, physical abuse, forced marriage and child marriage. This is a hospital-based prospective study conducted for a period of 6 months (from January 1st 2023 till the end of June 2023). It was collected from the records, which is secondary data, of all the gender-based violence cases being presented to the One-Stop Crisis Management Center (OCMC) of the provincial hospital of Bagmati Province. The level of violence was identified by the medico-legally trained medical officers and nursing personnel (allocated as the OCMC head) of the hospital. The data collected were grouped as under physical violence, domestic violence, sexual violence, child marriage, mental abuse and other violence. The data was analyzed using SPSS-16. Out of the total cases (156) which arrived to the OCMC, maximum cases (39.10%) were in the age group of 15-30 years. Majority of the cases (94.87%) were females. The gender-based violence cases were predominantly observed on janajatis (58.97%). Sexual violence accounted for 45.51% of the total number of cases. Majority of the perpetrators of violence (17.94%) was accounted by relatives. The highest number of gender based violence cases (32.69%) returned to respective organizations. The OCMC of the provincial hospital provides a one-door system for the effective management of the cases. Strict plans and policies need to be made by the government to reduce the burden of violence in females. More centers need to be established throughout the country so that there is more coverage of the cases.